Assisted Ventilation in Patients With Acute Respiratory Distress Syndrome: Lung-Distending Pressure and Patient-Ventilator Interaction. Issue 2 (April 2016) - Doorduin, Jonne; Sinderby, Christer A.; Beck, Jennifer; van der Hoeven, Johannes G.; Heunks, Leo M. A.
Abstract : Surv Anesthesiol 2016;60(2):50–51 Patients with acute respiratory distress syndrome (ARDS) are often on controlled mechanical ventilation, which has been associated with diaphragm weakness. Assisted mechanical ventilation may circumvent this issue, as it is more similar to natural respiratory variability and may give patients the "freedom" to control their ventilator assist.